2004
DOI: 10.1002/ajmg.b.30074
|View full text |Cite
|
Sign up to set email alerts
|

Linkage to chromosome 14q in Alzheimer's disease (AD) patients without psychotic symptoms

Abstract: Cases of early onset AD have been attributed to three genes, PSEN1, PSEN2, and APP, while the only gene consistently associated with late onset AD (LOAD) is APOE. Several genome scans have now been performed for LOAD with inconsistent findings in several genomic regions, possibly reflecting the underlying genetic heterogeneity. Many lines of evidence suggest that the absence or presence of psychotic symptoms, common in AD, might delineate distinct etiologic disease subtypes. We have performed a genome scan of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 45 publications
0
26
1
Order By: Relevance
“…Avramopoulos and colleagues [41] reported significant evidence for linkage near PSEN1 at 14q24 related to a phenotype that included psychosis. Although 14q32.12 is some distance away (~33 cM) from 14q24 and the PSEN1 gene, we as others [16] observed significant linkage at this locus.…”
Section: Discussionmentioning
confidence: 99%
“…Avramopoulos and colleagues [41] reported significant evidence for linkage near PSEN1 at 14q24 related to a phenotype that included psychosis. Although 14q32.12 is some distance away (~33 cM) from 14q24 and the PSEN1 gene, we as others [16] observed significant linkage at this locus.…”
Section: Discussionmentioning
confidence: 99%
“…Familial aggregation studies of probands and siblings with AD have shown a higher chance of concordance for AD+D in siblings and probands than by chance alone [33]. Using genome scans of 148 AD pedigrees, Avramopoulos and colleagues [34] identified a locus on chromosome 2p that is linked with AD+D and a locus on 14q that predisposes individuals to a form of dementia without comorbid psychotic features.…”
Section: Geneticsmentioning
confidence: 99%
“…Most studies with both late and early/mixed age at onset datasets showed separate results for these different age groups [ 126,129,132,133 ]. Where applicable, the age subsets for the results are shown in Tables 3 -8. Many of the studies performed subset analyses based on ApoE genotypes [ 117,124,126,127,136 ], though their definitions of E4+ (ApoE ε4 +) or E4− subsets varied between the studies.…”
Section: ) Role Of Apoe For the Diagnosis Of Ad And As A Premorbid Mmentioning
confidence: 99%
“…The autopsy confirmed subset also had another downstream region on chromosome 9q with evidence of linkage. In the substantially overlapping dataset analyzed by Myers et 3) Alternative analytical methods to detect risk loci for LOAD-In addition to the 9 whole genome linkage or association analyses in predominantly non-overlapping samples [ 117,119,121,123,126,127,129,130,132,135,136 ], seven linkage studies are presented here, which utilized alternative analytical strategies to re-assess the data in overlapping datasets [ 122,124,125,128,131,133,134 ]. We will briefly discuss their approaches and results, as they bring potential new understanding and evidence to the LOAD risk loci.…”
Section: C) Chromosome 12mentioning
confidence: 99%
See 1 more Smart Citation